Pengaruh Pemberian Biourine Sapi Pada Sistem Hidroponik Terhadap Pertumbuhan dan Hasil Tanaman Kangkung Darat - I Putu Sujana; Cokorda Javandira; Listihani; Ignasius Sandriawan (Fakultas Pertanian dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
This study aims to determine the effect of giving different cow biourine in the hydroponic system on the growth and yield of land kangkung plants to get the right cow biourine administration in the hydroponic system so that the best growth and yield of kale plants is obtained. The design used in this study was a randomized block design (RAK). With 6 treatments of giving cow biourine, K1: cow biourine giving 100 ml/1 liter of water, K2: 200 ml/1 liter, K3: 300 ml/1 liter, K4: 400 ml/1 liter, K5: 500 ml/1 liter and K6: 600 ml/1 liter of water. With 4 replications and 24 trials. The conclusion of this study was that the highest yield of land kangkung in a hydroponic system was obtained by giving biourine 300 ml/1 liter of water such as the highest plant height (K3 = 45.80 cm), the highest number of leaves (K3 = 15.00 pieces), leaf area (K3=102.25 cm), total wet weight of plants (K3=40.03 g) and oven-dry weight of plants (K3=2.19 g). giving biorine 300 ml/1 liter of water is the right way to get the best yield of land kale in a hydroponic system compared to giving 100 ml/1 liter of water; administration of 200 ml/1 liter of water; administration of 400 ml/1 liter of water; administration of 500 ml/1 liter of water; administration of 600 ml / 1 liter of water.